ANALISIS PENERAPAN PROBLEM BASED LEARNING DALAM MENSTIMULUS BERPIKIR KRITIS IPS DI SMP - Reza Riskiani; Yadi Suryadi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Social Studies learning at SMP Negeri 14 Semarang is still dominated by conventional memorization-based methods, so students' analytical reasoning has not developed optimally. This descriptive qualitative research aims to analyze the effectiveness of the Problem Based Learning (PBL) syntax in stimulating critical thinking skills based on five of Robert Ennis's indicators framed by the standards of the National Council for the Social Studies (NCSS). The determination of study participants, namely Social Studies teachers and eighth-grade students, was carried out using purposive sampling techniques. The stages of data collection were realized through participant observation, semi-structured interviews, and documentation, and were then analyzed interactively and validated through triangulation. The results of the study show that the implementation of PBL has empirically been proven to meet all five critical thinking indicators through adaptive teacher scaffolding and students' digital literacy collaboration. Nevertheless, the practice of the PBL model is hindered by time management during 'peak hours', limitations of classroom infrastructure, as well as internal student constraints (free-rider effects, low interest, digital distractions, and pedagogical trauma). In conclusion, PBL successfully transforms rote learning into a rational and objective understanding of history, requiring a harmonious synergy between instructional design, supporting facilities, and the socio-emotional readiness of students.